A review of the requirements for injection systems and the effects of fuel quality on particulate emissions from GDI engines - Leach, F; Knorsch, T; Laidig, C; Wiese, W (Society of Automotive Engineers, 2018)
Particulate emissions from Gasoline Direct Injection (GDI) engines have been an important topic of recent research interest due to their known environmental effects. This review paper will characterise the influence of different gasoline direct injection fuel systems on particle number (PN) emissions. The findings will be reviewed for engine and vehicle measurements with appropriate driving cycles (especially real driving cycles) to evaluate effects of the fuel injection systems on PN emissions. Recent technological developments alongside the trends of the influence of system pressure and nozzle design on injector tip wetting and deposits will be considered. Besides the engine and fuel system it is known that fuel composition will have an important effect on GDI engine PN emissions. The evaporation qualities of fuels have a substantial influence on mixture preparation, as does the composition of the fuel itself. Recently a number of studies have attempted to link fuel composition with PN emissions, developing a variety of indices including the PM index (Aikawa et al.) and the PN index (Leach et al.). An extensive literature search has been carried out and the PN index evaluated against these data. In addition the PM index and PN index are compared. The results of the review show that the Aikawa index should be applied when the fuel quality is known by lab reports, whereas the Leach index is relevant when only minimal information about a fuel is known, even the latter giving a relatively good prediction of PN emission trends from fuels in GDI engines.